The effect of teaching visual programming languages on developing students programming skills - AlQahtani, Amsha Munahi (Journal of Educational and Psychological Sciences, 2021)
The purpose of this research is to examine the effectiveness of the Scratch language in developing programming skills among the third intermediate grade students in Dammam (Saudi Arabia). To achieve the research goal, the researcher used the experimental methodology with its semi-experimental, the research population included all third intermediate grade students totaling (3437 students). The sample was selected through random cluster way, where it consisted of (31) third intermediate grade students. The research instrument was sort of a notecard. It included three main programming skills, with each skill includes a group of sub-skills, then the researcher applied the research instrument to the research sample, with the aim of determining the pre-level of students programming skills, then the group was exposed to the independent variable, then the research instrument was applied to the group itself in order to find out the difference between the pre and post level of the students. Research results: - The effectiveness of the Scratch program in developing programming skills among third intermediate grade students in Dammam. - There is a statistically significant difference at the level of (0.05) between the average grades of female students in pre and post-performance with regard to programming skills. The study recommended the need to review the Scratch language and to teach it to students the early intermediate grade students in education.